THE TRAJECTORY OF A HEROINE IN ADAPTED SPORT (Fiep Bulletin - online, 2015)
A configuration called Adapted Sport concentrate athletes in its organization, favoring the relations between members in the constitution of this specific group, without that the total set of members, or either, other disable people to participate.  In the instance of the high performance, the institution promotes the competition, analysis, comparison and classification of performances and individuals.  However, also it provides the meeting of identification and the construction of the belonging idea of the group by rules and rituals (training and competitions), therefore "the individuals are always presented in configurations and these always are formed by individuals" (ELIAS; DUNNING, 1992, p. 291).  Transformed into spectacle by media, the sport, as sign of the contemporary society, sells the good life idea, self confidence, to be victorious, to be transmitted as ideal for the average of the population achieve (RUBIO, 2003). When telling a part of the history from a pioneering paralympic athlete in our country, we did not discover only the concrete facts of gotten results, but the human beings who surround our heroine.  On this configuration that the individual is part of is formed by the emotions structure. Sensitivity and behavior are changes and variations' component influencing the individual in self-constitution (ELIAS, 1994).
Keywords: Adapted Sport-configuration-paralympic athlete